2006
DOI: 10.1111/j.1834-7819.2006.tb00398.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the leaf gauge and anterior jig on jaw muscle electromyography and condylar head displacement: a pilot study

Abstract: Background: A leaf gauge and an anterior jig may be used to assist the recording of a reproducible jaw position for restorative and prosthodontic treatment. This study investigated possible condylar displacement using an opto-electronic jaw-tracking device and a leaf gauge or anterior jig. The effect of a leaf gauge and anterior jig on jaw muscle electromyography was also examined. Methods: Five healthy adults without symptoms of temporomandibular disorders were selected. Condylar displacement during clenching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 31 publications
1
7
0
2
Order By: Relevance
“…Santosa et al 19 demonstrated that a neuromuscular device eliminates the posterior occlusal contacts, causing a de-programming of the proprioceptive memory of the periodontal ligament and promoting the relaxation of the masticatory muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Santosa et al 19 demonstrated that a neuromuscular device eliminates the posterior occlusal contacts, causing a de-programming of the proprioceptive memory of the periodontal ligament and promoting the relaxation of the masticatory muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, posterosuperior condylar displacement reaches an average of 0.81 mm during maximal intercuspal clenching (Santosa et al;2006), whereas the amount of tooth movement under occlusal loads is less than 0.15 mm on average (Satsuma et al, 2002). The discrepancy between condylar and dental displacements can also cause the proximity of the posterior part of the mandibular corpus to the maxilla, and can contribute to the slanted bite-force distribution.…”
Section: Article In Pressmentioning
confidence: 99%
“…27 In addition, another research showed the use of ABS does not lead to the changes of condyles position with maximum bite force. 28 Some of literatures and researches also still recommend the use of ABS, but not more than 2 weeks with closely monitored. 4,11,24,29 For occlusal bite registration, this case report used MI position, because patients have complete teeth and stable occlusion.…”
Section: Resultsmentioning
confidence: 99%